Determining Quantity Model of Built-Up Occupancy Residential in Musi Banyuasin District - Mutaqin, Zenal; Agustian, Endy; Imron, Imron; Muslim, Bukhori; Norman, Norman (Jurnal Planologi, 2024)
ABSTRACTThe determination of the quantity of dwellings in Musi Banyuasin district is a form of activity in seeing the development of the number of dwellings on built-up residential land when the existing data on the quantity of dwellings needed for the base year has not been obtained during secondary data collection. The importance of existing occupancy quantity data in planning activities, of course, is as a basis for determining the level of future occupancy shortages (projections). The purpose of this research is to determine the existing data on the number of dwellings in 2022 as an alternative form of providing the quantity of dwellings on built-up settlement land that will be used as planning data in Musi Banyuasin district. The method used is a quantitative approach with analytical methods, statistical, spatial and technical. Based on the results of the analysis, the quantity of dwelling units in Musi Banyuasin district on 7,528 hectares of built-up settlement land resulted in 205,962 dwelling units spread across all sub-districts with an average dwelling area of 148 square meters per house consisting of 124,441 households. These results are based on an assessment of the standard deviation and correlation level of 3 alternative comparison data, namely 213,645 dwelling units and 243,227 dwelling units, both of which have standard deviation and correlation values below the value of alternative 1.Keywords:  Settlement; Residential; Decision; Statistics; TechnicalABSTRAKPenentuan jumlah hunian di Kabupaten Musi Banyuasin merupakan bentuk kegiatan untuk melihat perkembangan jumlah hunian di lahan permukiman terbangun ketika data eksisting mengenai jumlah hunian yang dibutuhkan untuk tahun dasar belum diperoleh selama pengumpulan data sekunder. Pentingnya data kuantitas hunian eksisting dalam kegiatan perencanaan tentu saja sebagai dasar untuk menentukan tingkat kekurangan hunian di masa depan (proyeksi). Tujuan dari penelitian ini adalah untuk menentukan data eksisting mengenai jumlah hunian pada tahun 2022 sebagai bentuk alternatif penyediaan kuantitas hunian di lahan permukiman terbangun yang akan digunakan sebagai data perencanaan di Kabupaten Musi Banyuasin. Metode yang digunakan adalah pendekatan kuantitatif dengan metode analisis, statistik, spasial, dan teknis. Berdasarkan hasil analisis, jumlah unit hunian di Kabupaten Musi Banyuasin pada lahan permukiman terbangun seluas 7.528 hektar menghasilkan 205.962 unit hunian yang tersebar di seluruh kecamatan dengan rata-rata luas hunian sebesar 148 meter persegi per rumah yang terdiri dari 124.441 rumah tangga. Hasil ini didasarkan pada penilaian terhadap nilai standar deviasi dan tingkat korelasi dari 3 data perbandingan alternatif, yaitu 213.645 unit hunian dan 243.227 unit hunian, di mana keduanya memiliki nilai standar deviasi dan korelasi di bawah nilai alternatif 1.Kata kunci: Permukiman; Hunian; Keputusan; Statistik; Teknis.